2023
DOI: 10.3389/fimmu.2022.1051059
|View full text |Cite
|
Sign up to set email alerts
|

The impact of supervised physical exercise on chemokines and cytokines in recovered COVID-19 patients

Abstract: COVID-19 is an infectious disease caused by the SARS-CoV-2 virus, which induces a high release of pro-inflammatory chemokines and cytokines, leading to severe systemic disorders. Further, evidence has shown that recovered COVID-19 patients still have some symptoms and disorders from COVID-19. Physical exercise can have many health benefits. It is known to be a potent regulator of the immune system, which includes frequency, intensity, duration, and supervised by a professional. Given the confinement and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Exercise has been shown to significantly impact neuroendocrine effects, inflammatory markers and the immune system in individuals with COVID-19. Multiple studies found that moderate exercise reduced symptoms, severity, and recovery time in COVID-19 patients [20][21][22]. A study reported that two weeks of moderate-intensity aerobic exercise decreased the severity and progression of COVID-19-associated disorders and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise has been shown to significantly impact neuroendocrine effects, inflammatory markers and the immune system in individuals with COVID-19. Multiple studies found that moderate exercise reduced symptoms, severity, and recovery time in COVID-19 patients [20][21][22]. A study reported that two weeks of moderate-intensity aerobic exercise decreased the severity and progression of COVID-19-associated disorders and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Filgueira et al. suggested that supervised controlled exercise could balance the inflammatory peripheral components, mitigating the inflammatory process associated with PCC and its consequences ( 27 ). In patients with severe SARS-CoV-2 infection in the acute phase, immunotherapy is the cornerstone of drug therapy ( 28 ) with an important role for anti-IL-6 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…According to Nieman and Sakaguchi [28], adequate participation in moderate to vigorous physical activity (MVPA) is linked to a lower likelihood of experiencing acute respiratory infections (ARIs) [28]. Filgueira et al [29] showed that a supervised exercise protocol for 12 weeks could alleviate inflammation in adults after COVID-19 compared to an unsupervised home exercise protocol [29]. However, Libardi et al (2012) and the study of Khajeh Landi et al (2020), which did not report a significant decrease in serum levels of IL-6 [30,21].…”
Section: Discussionmentioning
confidence: 99%